Theoretical and experimental study on interface stiffness measurement of rough surface using improved acoustic model. (1st March 2023) - Yuan, Bo; Wang, Yingquan; Sun, Wei; Mu, Xiaokai; Zhang, Chao; Sun, Qingchao
Graphical abstract: Highlights: Presented an acoustic model considering contact interface and boundary effects integrating microwave transmission line theory. Analyzed the relationship between contact parameters and elastic wave energy transfer. Constructed a new interface stiffness detection index to ensure the robustness of the detection results. Compared the robustness of different detection indexes and the uncertainty of different detection methods. Abstract: Structural health monitoring (SHM) of interface stiffness is of great significance in many fields, such as accurate rotor dynamics modeling and interface friction performance analysis. Acoustic wave is an important interface detection method. However, the interface mechanics and elastic wave theory are relatively independent, and the interaction mechanism between the contact asperity parameters and the energy transfer of elastic waves has not been thoroughly explored. The existing interface stiffness detection indexes do not consider the uncertainty of boundary parameters, which easily leads to the degradation of detection performance and limits the promotion of interface stiffness detection. In this paper, we proposed an acoustic model considering contact interface and boundary effects integrating microwave transmission line theory. A new interface stiffness detection index is constructed to ensure the robustness of the detection results. The relationship between contact parameters and elastic wave energy transfer is analyzed, and the robustness of different detection indexes and the uncertainty of different detection methods are compared. The experimental results of the pressure-bearing connection structure are obtained to verify the correctness of the acoustic model and the feasibility of the detection method. The proposed method is further applied to multi-bolted structures, and the robustness of the proposed method is discussed. The results show that the proposed method has the ability of in-situ interface stiffness detection and potential engineering utility.